2021
DOI: 10.3389/fpsyg.2021.638274
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Alliance in COVID-19 Era Remote Psychotherapy Delivered to Physically Ill Patients With Disturbed Body Image

Abstract: The COVID-19 pandemic outbreak has led to a general reorganization of health services and an increase in outpatient telemedicine in mental healthcare for physically ill people. Current literature highlights facilitators and obstacles concerning the use of new technologies in psychotherapy, an underrated topic of research in the context of supportive expressive psychotherapy. More insight is needed to explore the characteristics of video in therapeutic alliance for treatment of specific mental disorders experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Generally, however, it is believed that body dissatisfaction and appearance concerns have increased with the use of video conferencing through the pandemic (Pikoos et al, 2021; Sarangi et al, 2022; Stewart & Stapleton, 2022; Plumley et al, 2021). In terms of therapeutic engagement, Grignoli et al (2021) suggest that the effect of mirroring through a self‐view video screen for those experiencing self and/or body image disturbance can be disorientating. The self‐view image becomes the focus, facial expression is contrived and the quality of the therapeutic alliance diminishes.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, however, it is believed that body dissatisfaction and appearance concerns have increased with the use of video conferencing through the pandemic (Pikoos et al, 2021; Sarangi et al, 2022; Stewart & Stapleton, 2022; Plumley et al, 2021). In terms of therapeutic engagement, Grignoli et al (2021) suggest that the effect of mirroring through a self‐view video screen for those experiencing self and/or body image disturbance can be disorientating. The self‐view image becomes the focus, facial expression is contrived and the quality of the therapeutic alliance diminishes.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinicians, including psychologists, rapidly shifted from the traditional face-to-face (FTF) approach to web-based videoconference psychotherapy (VCP) [1]. Psychologists began to rely exclusively on video and audio channels to support their patients during the pandemic [2]. Although the COVID-19 pandemic encouraged psychologists to undertake VCP as a temporary alternative to FTF treatment, the uptake of such approaches was already rising [3], especially in remote areas where access to health care services is limited [4].…”
Section: Introductionmentioning
confidence: 99%
“…A client's relationship with their therapist, often referred to as a therapeutic bond or alliance, is a vital aspect of the psychotherapeutic process (Grignoli, Arnaboldi & Antonini, 2021). Emerging research on the impact of COVID‐19 on the therapeutic alliance has suggested what was vital to successfully navigating therapy during the pandemic (Cioffi et al ., 2020; Fernández‐Álvarez & Fernández‐Álvarez, 2021; Geller, 2021; Grignoli, Arnaboldi & Antonini, 2021; Zubala & Hackett, 2020; van Lotringen et al ., 2021). Several studies found that therapeutic alliance was not significantly altered by online therapy delivery (Earle & Freddolino, 2022; Eichenberg et al ., 2022; Lange et al ., 2022; Leuchtenberg, Gromer & Käthner, 2023; Sagui‐Henson et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A client's relationship with their therapist, often referred to as a therapeutic bond or alliance, is a vital aspect of the psychotherapeutic process (Grignoli, Arnaboldi & Antonini, 2021). Emerging research on the impact of COVID-19 on the therapeutic alliance has suggested what was vital to successfully navigating therapy during the pandemic (Cioffi et al, 2020;Fern andez-Álvarez & Fern andez-Álvarez, 2021;Geller, 2021;Grignoli, Arnaboldi & Antonini, 2021;Zubala & Hackett, 2020;van Lotringen et al, 2021). Several studies found that therapeutic alliance was not significantly altered by online therapy delivery (Earle & Freddolino, 2022;Eichenberg et al, 2022;Lange et al, 2022;Leuchtenberg, Gromer & Käthner, 2023;Sagui-Henson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%